2010
DOI: 10.1371/journal.pcbi.1000748
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Physical Embedding of Topologically Complex Information Processing Networks in Brains and Computer Circuits

Abstract: Nervous systems are information processing networks that evolved by natural selection, whereas very large scale integrated (VLSI) computer circuits have evolved by commercially driven technology development. Here we follow historic intuition that all physical information processing systems will share key organizational properties, such as modularity, that generally confer adaptivity of function. It has long been observed that modular VLSI circuits demonstrate an isometric scaling relationship between the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
474
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(503 citation statements)
references
References 67 publications
29
474
0
Order By: Relevance
“…Brain regions also exhibit cytoarchitectonic differences (12). A modular structural wiring network (i.e., white matter tracts), with dense connectivity within modules and weak connectivity between modules, has also been consistently found in human brain imaging data (5,6,13,14). Finally, the brain's functional architecturehow the brain's modules interact to produce cognition-appears modular (7,(15)(16)(17).…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Brain regions also exhibit cytoarchitectonic differences (12). A modular structural wiring network (i.e., white matter tracts), with dense connectivity within modules and weak connectivity between modules, has also been consistently found in human brain imaging data (5,6,13,14). Finally, the brain's functional architecturehow the brain's modules interact to produce cognition-appears modular (7,(15)(16)(17).…”
mentioning
confidence: 69%
“…Moreover, a double dissociation was found between two modules, such that, for both modules, damage to a node in one module only caused dysfunction (i.e., a decrease in functional connectivity) in the damaged module, suggesting their autonomy (78). Finally, empirical functional connectivity studies have shown that modules are weakly functionally connected to each other, likely because their computations are predominantly distinct, suggesting modular function (6,7,16,36,79). However, connections do occur between modules that transfer information between the modules and influence local activity in the modules, potentially increasing the modules' computational loads (6,7,16,27,28,36,(80)(81)(82)(83).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This hierarchical scaling of communication is a well-known pattern in circuit design called Rent's rule [4], where p ¼ 1/D w is Rent's exponent. 1 This pattern is not unique to circuits and has been shown to occur in many biological networks [12][13][14][15]. Vascular systems correspond to a special case, where w i ¼ 1 for all i.…”
Section: Unified Model Of Network Scalingmentioning
confidence: 99%